Project Report Safety and Security System In Multi-Axle Buses - ANJALI U HALDANKAR,MONIKA M,ANKIT KUMAR NAIR and ANITHA N. (2013)
INTERNAL GUIDE : ARSHIYA SULTANA. EXTERNAL GUIDE:KRISHNAMURTHY M. USN NO : 1MJ10EC009,1MJ10EC050,10EC012,1MJ11EC400 CARRIED OUT AT : Electrono Solutions Pvt Ltd Vinayaka Layout Immadihalli Road Whitefield Bangalore-66 ACC N : PR2131
Keywords: Safety and Security System In Multi-Axle Buses